Effect of plyometric training on athletic performance in preadolescent soccer players - Michailidis, Y. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to investigate the effectiveness of plyometric training on performance of preadolescent soccer players. 21 players assigned to two groups: jumping-group (JG, n = 11) and control-group (CG, n = 10). Training program was performed for 10 weeks. Anaerobic power performances were assessed by using standing long jump (SLJ), 10 m and 30 m sprint. In the JG the performance at the long jump was increased significantly (P = 0.031). Also the performance of JG increased at 30m sprint running by 7.2 % (P < 0.001). None of the variables tested in the CG demonstrated difference between the pre-test and the post-test. Our results indicate that plyometric training can improve running performance at 30 m sprint and the performance at standing long jump in preadolescent soccer players.